Molecular characterization of a novel aspartyl aminopeptidase that contributes to the increase in glutamic acid content in chicken meat during cooking - Hitomi Yuhara; Akira Ohtani; Mami Matano; Yutaka Kashiwagi; Kenji Maehashi (Food Chemistry: Molecular Sciences, 2021)
The enzyme involved in the increase in glutamic acid content in chicken meat during cooking was identified and characterized. Chicken homogenate produced significantly more free glutamic acid and exhibited higher glutamyl p-nitroanilide (Glu-pNA) hydrolyzing activity than beef when heat cooked. Amino acid sequencing revealed the presence of aspartyl aminopeptidase (DNPEP) in chicken meat. Using RT-PCR, DNPEP gene expression was detected in chicken breast and thigh muscles, liver, and small intestine, together with various other peptidase genes. Full-length DNPEP cDNA was cloned, and recombinant chicken DNPEP (cDNPEP) was expressed in Escherichia coli. cDNPEP showed five-fold higher activity against Glu-pNA than against aspartyl-pNA, which represents a different substrate specificity than observed for recombinant bovine DNPEP (bDNPEP). The Km values of both DNPEPs with Glu p-NA substrates indicated a higher affinity of cDNPEP for glutamyl residues. This unique substrate specificity of cDNPEP contributes to efficient glutamic acid production in chickens.